THE EFFECT OF PROMOTION, BRAND IMAGE AND SERVICE QUALITY ON CUSTOMER LOYALTY AT KENTUCKY FRIED'S FAST FOOD RESTAURANT CHICKEN (KFC) IN LHOKSEUMAWE CITY - Wahyu Syahputra; Hamdiah; Adnan; Rusydi (CV. Radja Publika, 2026)
This study aims to analyze the effect of Promotion, Brand Image, and Service Quality on Customer Loyalty at Kentucky Fried Chicken (KFC) fast-food restaurant in Lhokseumawe City. Customer loyalty is an important factor in maintaining business sustainability amid increasingly intense competition in the fast-food industry. Companies are required to implement effective marketing strategies and provide high-quality services in order to retain customers and enhance competitiveness. This research employed a quantitative approach using a survey method. The population of this study consisted of KFC customers in Lhokseumawe City. The sample comprised 120 respondents selected through purposive sampling, with the criterion that respondents had made purchases more than once. Data were collected through questionnaires developed based on the indicators of each research variable. The data were then analyzed using multiple linear regression analysis with the assistance of SPSS software. The results show that partially, service quality has a positive and significant effect on customer loyalty. This indicates that better service quality leads to higher customer loyalty. Meanwhile, promotion and brand image do not have a significant effect on customer loyalty in Lhokseumawe City. Simultaneously, promotion, brand image, and service quality collectively influence customer loyalty. The findings of this study are expected to provide valuable insights for KFC management in formulating more effective marketing strategies to improve customer loyalty.